A influência do processo de produção de scaffolds na regeneração óssea - Vallejo, Mariana Costa da Silva (2014)
The raising level of bone defects worldwide has become a major concern of public health. Autografts, allografts and xenografts are some alternatives that are currently being used to overcome bone related problems. However the risks of infection and immunological response from the patient are very high. To surpass these handicaps, new biodegradable and biocompatible structures (scaffolds) have been produced in the area of tissue engineering to be used as temporarily bone substitutes. These structures allow cell adhesion and proliferation, while giving mechanical support to the newly bone formation. Several biocompatible materials have been used so far for scaffolds production. Nevertheless it is fundamental that the right production method is chosen, since it will influence the regenerative process. In this study a chitosan/alginate/β-TCP scaffold was produced by three different techniques: rapid prototyping using a Fab@home 3D printer, freeze-drying and foam replication method. The scaffolds were characterized by Fourier transformed Infrared spectroscopy, X-ray diffraction, Energy dispersion Spectroscopy, Scanning Electronic microscopy and water contact angle. Moreover, the porosity, mechanical properties, swelling profile, and degradation behavior of the different scaffolds were also characterized. The cytotoxic profile of the scaffolds was studied using a rezazurin assay. The cellular adhesion, proliferation and internalization in the scaffolds were studied by optical, scanning electronic and confocal laser scanning microscopy. The antimicrobial properties of the different scaffolds were tested against Staphylococcus Aureus, using a Kirby-Bauer disk diffusion method. All the results revealed that the chitosan/alginate/β-TCP scaffolds produced by rapid prototyping had the most suitable properties for being applied in bone regeneration.